Redefining Kirant Rai Folk Narratives: Politics of Gender and Self-Identity - Rai, Prakash (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2023)
This paper examines how Kirant Rai folk narratives influence gendered representation, self-identity, and socio-political dynamics within the community. Particularly, it centers on four significant folk narratives: Hechchhakuppa, Yala Hang and Sakelung, Sawanam, and Sumdima and Paruhang, which I collected through extensive interviews conducted with knowledgeable elders, Mangpa, and elder community members. To analyze these narratives and uncover their thematic implications, the study employs Alan Dundes' functional theory and incorporates the political ideas of Ranciere. The primary data for this research consists of narrative texts supplemented by secondary data sourced from libraries and online resources. This study reveals that these folk narratives have played a pivotal role in shaping gendered representation, self-identity, and the individually valued roles that contribute to the socio-political dynamics prevalent in the community since the narratives' inception. By uncovering these findings, this research contributes to a deeper understanding of the cultural significance and social dynamics of the people. It highlights the transformative power of these folk narratives and their influence on various aspects of the community's social fabric by broadening knowledge and appreciation of the Kirant Rai cultural heritage while, at the same time shedding light on the intricate interplay between narratives, gender roles, self-perception, and sociopolitical dynamics.